(untitled) (Nepal Medical College Journal, 2021)
Tonsillectomy is the most commonly performed surgery. Cold dissection tonsillectomy remains as the gold standard for tonsil removal, although it may increase risk for complication. Coblation tonsillectomy is a new technique .There are studies comparing these two method of surgery and have shown coblation technique to cause less postoperative pain, less intra operative time along with less intra and postoperative blood loss. In contrary few studies have shown it to be ineffective in reducing postoperative bleeding. Hence more studies are still required. Thus the objective of the present study was to compare coblation and cold dissection techniques outcome among tonsillectomy patients at Birat Medical College and Teaching Hospital. The study intended to determine and compare the intraoperative time, intra operative blood loss and postoperative pain in coblation and cold dissection tonsillectomy. This is a hospital based cross sectional comparative study. Eighty six patients underwent tonsillectomy during the study period of one year (15th Feb 2020 to 14th Feb 2021) in the department of ENT HNS, Birat Medical College and Teaching Hospital. Among 86 patients, 43 underwent cold dissection and 43 coblation tonsillectomy. Method of surgery was based on odd and even serial number of the patients during presentation. This study showed that intra operative time, intraoperative blood loss and post operative pain score was 16.77±2.7mins, 36.51±128ml and 6.28 respectively in coblation method and 37.84±3.1 mins, 101.4±12.7ml and 7.88 respectively in cold dissection method. Hence coblation method is a safer and effective method of tonsillectomy compared to cold dissection which ultimately leads to less post operative analgesics demands and early recovery.